Teori Pertukaran (Natural Certainty Contract) Dan Teori Percampuran (Natural Uncertainty Contracts) - Nur Azizah Assaalimah (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
Introduction/Main Objective: This study aims to determine the theory of exchange (natural certainty contracts) and the theory of mixing (natural uncertainty contracts). Background problems: the theory of exchange (natural certainty contracts) and the theory of mixing (natural uncertainty contracts) are basic concepts in a transaction muamalah, especially in transactions in Islamic banking. Therefore, a deeper understanding of the concepts of exchange theory and mixed theory in Islamic economics is needed first before discussing Islamic banking (real sector based banking). Research Methods: This type of research is included in the category of library research, using a qualitative approach. Findings/Results: Judging from the level of certainty of the results that will be obtained, the tijarah contract can be divided into two, namely in terms of the theory of exchange (natural certainty contract) and in terms of mixed theory ( natural uncertainty contracts). Conclusion: when talking about Islamic finance and banking which cannot be separated from the study of transactions that occur in the real sector, then the issue of contract is the key in these transactions. In the discussion of the contract, it can be seen from the problem of whether or not there is compensation promised by one of the parties. in this case, the contract is divided into two, namely the tabarru' contract and the tijarah contract. In the tabarru' contract, each type of agreement involves not-for-profit transactions (non-profit transactions). But in the tijarah contract, all types of contracts are included in the for profit transaction function. Judging from the level of certainty of the results to be obtained, the tijarah contract can be divided into two, namely in terms of the theory of exchange (natural certainty contracts) and in terms of the theory of mixing (natural uncertainty contracts). These two concepts are the basis in a muamalah transaction, especially in transactions in Islamic banking.